THE CONCEPT OF GHOSРITАЛЬАЛЬ RÉDÉGICAL AND ITS ESSENCE (American Journal of Interdisciplinary Research and Development, 2025)
This article presents the concept of geologic and its essence. It also identified the need to organize the educational process of students in hospitals and other health institutions, based on the interlinking of medicine and education. Similar and different features of therapeutic pedagogy, hospitable pedagogy, medical pedagogy, and inclusive pedagogy are highlighted.